2011
DOI: 10.1007/s11832-011-0375-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of slipped capital femoral epiphysis: Results of a survey of the members of the European Paediatric Orthopaedic Society

Abstract: AimTo determine current practice recommendations for the treatment of slipped capital femoral epiphysis (SCFE) among members of the European Paediatric Orthopaedic Society (EPOS).Materials and methodsA questionnaire with 4 case vignettes of a 12-year-old boy presenting with a stable and unstable SCFE. Each, stable and unstable slips, was of mild (20° epiphyseal-shaft angle) and of severe (60° epiphyseal-shaft angle) degree was sent to all members of EPOS in 2009 in order to ascertain their views on the best ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
2
41
0
2
Order By: Relevance
“…[1][2][3][4][5] This is often due to differences in opinion, which surgeons frequently accept because much of the literature underpinning practice is contradictory. 6 Another determinant is the poor quality of the evidence, which until recently almost universally involved observational case series.…”
Section: Cite This Article: Bone Joint J 2018;100-b:680-4mentioning
confidence: 99%
“…[1][2][3][4][5] This is often due to differences in opinion, which surgeons frequently accept because much of the literature underpinning practice is contradictory. 6 Another determinant is the poor quality of the evidence, which until recently almost universally involved observational case series.…”
Section: Cite This Article: Bone Joint J 2018;100-b:680-4mentioning
confidence: 99%
“…Only 8% of members indicated that they would deliberately avoid epiphyseal reduction. 3 An equivalent survey was conducted in America in 2005, with similar findings, although 27% of respondents did not routinely use the stable/unstable concept. 4 There are several studies (Table I) 5,6 documenting variable rates of AVN for unstable SCFEs treated by pinning in situ.…”
mentioning
confidence: 73%
“…Closed reduction and pinning in situ has been shown to be favoured in Europe as recently as 2011. 3 Our experience raises questions regarding this practice. We suggest that imaging of an unstable SCFE represents a snapshot of a dynamic process.…”
Section: Timing Of Procedures Following Onset Of Instability Rate Of Amentioning
confidence: 97%
See 1 more Smart Citation
“…3,4 SCFE can result in premature hip osteoarthritis (OA), 5 hip pain associated with loss of flexion and internal rotation, 6 and disability. 7 Premature OA, pain, and loss of hip range of motion (ROM) have been attributed to abnormal femoroacetabular geometry and mechanics 6 including that caused by SCFE.…”
mentioning
confidence: 99%